Hasil Belajar Fisika Melalui Pembelajaran Daring - Ratna Dwi Rahayu (SIMETRIS, 2022)
The online learning paradigm becomes an alternative at every level of education today. This study aimed to describe students' physics learning outcomes through online learning. The study, which involved 47 students Sekolah Tinggi Teknologi Ronggolawe Cepu Departmen of Mechanical Engineering Semester 1 , used observation sheet to collect data related to the online learning. Besides, the documentation of students' physics learning outcomes scores was collected to be analyzed by using descriptive statistics. The results of this study indicated that the average score of students’ physics learning outcomes through online learning was in Very Good category. Another finding from this study was that there were still 11% of students who needed physics tutoring. Thus, further research could explore the factors that hindered students' current understanding of physics learning.